1990
DOI: 10.1210/endo-126-2-1264
|View full text |Cite
|
Sign up to set email alerts
|

Estrous Cycle-Related Changes of High Affinity Luteinizing Hormone/Human Chorionic Gonadotropin Binding Sites in the Rat Uterus

Abstract: LH/human CG (LH/hCG) high affinity binding sites were detected in crude membrane preparations of rat uteri. There was little competition for receptor occupancy between hCG and ovine FSH (oFSH) (0.05%) and no competition between hCG and ovine PRL (less than 0.01%). No similar binding sites were detected in crude membrane preparation of heart, kidney, skeletal muscle, liver, and lung tissues. Concentrations of uterine unoccupied binding sites (RLH) were determined for each stage of the 4-day estrous cycle. The R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 0 publications
3
18
0
Order By: Relevance
“…After dioestrus, the expression level of Lhcgr dropped significantly back down to the pro-oestrus level of the next cycle. Our qRT-PCR results confirmed and extended findings in the mouse model reported by Bonnamy et al (1990), who observed a cyclic variation in LHCGR binding to radiolabelled hCG in the rat endometrium. The increased Lhcgr expression at the time of implantation provides further support for a possible role of LHCGR signalling at the maternal-fetal interface during embryo implantation in mice.…”
Section: Discussionsupporting
confidence: 90%
“…After dioestrus, the expression level of Lhcgr dropped significantly back down to the pro-oestrus level of the next cycle. Our qRT-PCR results confirmed and extended findings in the mouse model reported by Bonnamy et al (1990), who observed a cyclic variation in LHCGR binding to radiolabelled hCG in the rat endometrium. The increased Lhcgr expression at the time of implantation provides further support for a possible role of LHCGR signalling at the maternal-fetal interface during embryo implantation in mice.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported that the rat uterus contains LHR with an affinity constant for hCG that is analogous to that of rat ovarian receptors as shown in a previous study (3). The binding characteristics of these receptors were found to be similar to those reported for other animals (1,2), and these receptors have a high-binding-affinity constant and low-binding capacity.…”
Section: Discussionsupporting
confidence: 78%
“…Rao (1998) demonstrated that LH is able to induce cyclooxygenase 2 gene expression both in glandular epithelium and in stromal cells in human endometrium resulting in increased prostaglandin production (Zhoi et al 1997). The reported rise of uterine LHR/HCG receptor at metestrus in rats after ovulation (Bonnamy et al 1990) may be due to modulation of P 4 content (Bonnamy et al 1989). Our previous study also showed LH-induced increases in P 4 synthesis in mouse uterus at metestrus (Debnath et al 2000).…”
Section: Discussionmentioning
confidence: 66%
“…Contrary to this conventional belief, numerous studies demonstrated that the LH receptor (LHR)/HCG receptor is also present in a variety of non-gonadal tissues, particularly in the female reproductive tract (Bonnamy et al 1990, Reshef et al 1990, Lei et al 1993, Mukherjee et al 1994, Shemesh et al 1997, Ziecik et al 2005. Activation of this receptor in vivo and in vitro resulted in a wide variety of responses, which can be attributed to initiation and maintenance of pregnancy (Banaszak et al 2000, Srisuparp et al 2003, Lin et al 2005, Ziecik et al 2005.…”
Section: Introductionmentioning
confidence: 99%